(3HQgGf GdbQBfs - (3GdcQeGfj , HQgGf GdOjf CHh GdbGSe eMehO Hf MeRI Hf fUQ GdcQeGfj GdebQj GdTGaYj, JGL GdbQGA,J (B505 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GfRd GdbQGf Ydi eMeO djchf ddYGdejf fPjQkG hHYO aEf gPG cJGH GPcQ ajg GdGjGJ GdeJTGHgGJ GdJi JcQQJ ai GdbQGf CdaGXgG s
(3BNQgG (B:s
(3ShQI GdfGS bhdg CYhP HQH GdfGS Ke cQQ GdfGS NeS eQGJ bjd cQQ JHLdkG dge ceG SHb hbjd cQQ dEfaUGd cd Gjg ef GdGNQi hYWag Ydi GdeYhP efge jOd Ydi Pdc bGd GdeUfa JGL GdbQGA QMeg Gddg JYGdi ced cJGH HQgGf GdbQGfhGdMeO ddg Ydi cd MGd s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B168 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B161s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs